Industrial relations dominance in the ride sharing transportation apps - Alia, Mandra Nur; Suyanto, Bagong; Dugis, Vinsensio (Jurnal Studi Komunikasi, 2020)
The development of digitalisation has penetrated the transportation sector. Indonesia has become a market for ride-sharing startups which has proliferated in the past three years. This article aimed to understand the hidden interests and dominance occurring in industrial relations in the sharing economy system in Grab Indonesia, especially in GrabCar services. The formulations of the problem in this paper were: whether the cause of the conflict between Grab company and its business partners reflected the company's or business partners’ hidden interests? And then, what were the implications of the conflict on industrial relations for Grab and its partners?. This study used a qualitative approach with the Verstehen method to find the deepest and intersubjective meanings of social actions. This research applied the theory of conflict, industrial relations, and partnerships. Data sources in this study were primary sources in the form of interviews and secondary sources through newspapers, journals, books and webpages. The results showed that the cause of the conflict between Grab and its business partners revealed hidden interests of the company and some of its business partners. and also, conflicts caused imbalance and dominance of industrial relations in which the company has stronger power and authority than its business partners.